Cross-Сultural Values of Modern Student Youth: Resources of Multicultural Traditions of the Ukrainian Danube Region: Array - Kichuk, Nadia (Journal of Danubian Studies and Research, 2020)
Based on the analysis of philosophical, psychological and pedagogical, sociological, ethnical scientific literature, in which some aspects of the problem of cross-cultural contacts are highlighted, the content of the concept of “cross-cultural values of a personality” is clarified, the context of the specifics of the formation of cross-cultural values among student youth in the conditions of the dialogue of cultures of ethnic groups of the Ukrainian Danube Region is revealed.